أقسام الرحمة الإلهية وموجباتها:دراسة تطبيقية من خلال الآيات القرآنية: Divine mercy and its causes: An applied study through Qur’anic verses - Dr.Syed Asif Mahmood (AL-IDRAK JOURNAL, 2022)
This scholarly article includes the types of divine mercy and its causes, and there is no doubt in it that we all need and hope for Allah's mercy in this world and the hereafter. And His mercy engulfs everything and covers the whole world, because Allah has described Himself as the All Gracious and the All Compassionate, and He is the Most Merciful, Rather, more merciful than the mother to her child. So we have to know the types of His mercy and its causes, i.e. Who are the blessed people by the mercy of Allah in this world and the hereafter? and how can we have His mercy in both the worlds? The researcher will answer these questions by inferring from the Qur’anic verses so that all can take benefit from it; because we all require and in need of Allah's mercy, and we can’t live without His mercy even for a blink of an eye.